CIRURGIA ABDOMINAL POR ROBÓTICA: UMA REVISÃO INTEGRATIVA - Cardozo Vieira Rocha , Márllon (2024)
Introduction: Robotic surgery has advanced significantly, offering improved visualization and control compared to laparoscopy. However, its efficacy relative to traditional techniques remains debated, with clinical outcomes often being similar. Additionally, high technology faces challenges such as high costs and regional limitations. An integrative review is essential to assess the impact of robotic abdominal surgery on clinical outcomes and patient recovery. Objective: To analyze and synthesize the available evidence on the impacts of robotic abdominal surgery on clinical outcomes and patient recovery, compared to conventional surgical approaches. Methods: A systematic literature review was conducted using PubMed and Scopus databases, filtering for studies published within the last 6 years and of high methodological quality in English. Results and Discussion: Seven articles were selected for inclusion in this study. benefits and improving patient outcomes. Robotic abdominal surgery stands out for its precision and control, offering significant advantages over traditional techniques, particularly in complex procedures like hepatic and pancreatic resections. However, the prolonged operation time and high costs present significant challenges, and the additional clinical benefits of robotics over laparoscopy are not always clear. The learning curve for surgeons and the high initial cost are also barriers to widespread adoption. Future technological advancements and surgeon experience may enhance robotic effectiveness, but method selection should involve a balanced analysis of benefits and costs. Conclusion: Robotic surgery offers advancements in precision and control, particularly for complex procedures, but its clinical benefits are not always superior to laparoscopy. Laparoscopy remains an effective and less costly alternative. Wider adoption of robotics depends on technological advancements, cost reductions, and long-term data proving its benefits.